Learner autonomy assessment of English language teaching students in an international program in Thailand - Swatevacharkul, Rosukhon; Boonma, Nida (Indonesian Journal of Applied Linguistics, 2021)
The objective of this study was to assess learner autonomy of English Language Teaching students in terms of technical, psychological, political-philosophical, and sociocultural dimensions. The 19 participants were in their first semester of MA ELT, which is an international program in an international university in Thailand.Â  Among them, there were 15 Chinese, three Burmese, and one Thai. This study employed the explanatory mixed-methods design. First, Measuring Instrument for Language Learner Autonomy (MILLA) questionnaire (Murase, 2015) was used to collect quantitative data (QUAN). Then, a semi-structured interview with five participants was carried out to gather follow-up qualitative data (QUAL). The findings revealed that, on average, the students demonstrated a high level of autonomy in all four dimensions. The thematic content analysis generated four themes concerning each autonomy dimension: 1) the use of metacognitive strategies through professional goal setting 2) the intrinsic and extrinsic motivation in support of autonomous learning, 3) the teacher as authority partner in a negotiable learning process, and 4) the preference for self-dependence and collaborative learning. The results of the study can be pedagogically contributive to programs similar to the studyâ€™s context with regards to learner autonomy awareness and learner autonomy development.